2010
DOI: 10.1007/s10509-010-0363-5
|View full text |Cite
|
Sign up to set email alerts
|

Exact relativistic plasma waves in an electron–positron plasma

Abstract: Electrostatic plasma waves in an adiabatic electron-positron plasma are investigated nonperturbatively. It is shown that quasistationary large-amplitude waves with smooth as well as highly peaked profiles can appear. In the peaked waves, the electron and positron peaks may be separated by large distances, but no completely isolated solitonlike structures were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…When the speed of the charged object is high or when resonance occurs, the amplitude of the excited waves can become very large and relativistic effects can become significant [13], [23][24][25], [29,30]. In this paper, we investigate large-amplitude quasi-stationary plasma waves excited by and comoving with a charged rigid body by including relativistic effects, which can be expected to affect the interaction because of electron mass variation.…”
Section: Introductionmentioning
confidence: 99%
“…When the speed of the charged object is high or when resonance occurs, the amplitude of the excited waves can become very large and relativistic effects can become significant [13], [23][24][25], [29,30]. In this paper, we investigate large-amplitude quasi-stationary plasma waves excited by and comoving with a charged rigid body by including relativistic effects, which can be expected to affect the interaction because of electron mass variation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our results may be relevant to the cosmic relativistic double-layers (Carlqvist 1982) and the relativistic plasma structures that involve energetic plasma flows from accreting compact objects such as neutron stars and black holes (Dieckmann 2008). Furthermore, they may complement and provide new insights into recently published results (Lu et al 2010).…”
Section: Resultsmentioning
confidence: 70%
“…Subsequently and because of quantitative discrepancies between theory and experiment, the nonlinear ion-acoustic wave theory has been developed to include the effects of a finite ion temperature (Tappert 1972;Tagare 1973) and those due to a trapped electron population (Schamel 1972(Schamel , 1973 and high order nonlinearity (Watanabe 1978). On another side, a great deal of attention has been devoted to the study of different types of collective processes in electron-positron (e-p) and electron-positron-ion (e-p-i) plasmas (Lakhina and Buti 1981;Verga and Ferro Fontán 1984;Shukla et al 1986;Rizzato 1988;Tajima and Taniuti 1990;Salahuddin et al 1995;Popel et al 1995;Nejoh 1996aNejoh , 1996bLakhina and Verheest 1997;Gratton et al 1997;Onishchenko et al 1998;Liang et al 1998;Gahn et al 2000;Mushtaq and Shah 2005;Gill et al 2007;Mahmood and Akhtar 2008;Dubinov and Sazonkin 2009;Lu et al 2010;Pakzad and Javidan 2010;Ghosh and Bharuthram 2010). It is well known that when positrons are introduced into an electron-ion plasma the response of the latter changes significantly.…”
mentioning
confidence: 99%
“…[21] For example, Lu et al observed an exact relativistic plasma wave which is completely different from a soliton in an electronpositron plasma which the Sagdeev potential approach was applied to Ref. [22]. The one-dimensional (1D) propagation of ion acoustic solitary wave has been studied in different plasma systems by using the Korteweg-de Vries (KdV) equation.…”
Section: Introductionmentioning
confidence: 99%